Predicting the bond strength between steel wire and mortar based on interfacial porosity and shrinkage. (1st June 2023) - Zheng, Xuan; Zhang, Chi; Gao, Shengzhe; Wang, Fangzheng
Abstract: The interfacial bond strength, which is the key to predict pullout behavior of steel fiber/wire/rebar embedded in cement-based matrix, is usually determined by pullout tests. However, precise pullout test is difficult to be conducted, especially for steel fiber, due to the high accuracy requirements for equipment and operation process. In the present paper, a prediction model on interfacial bond strength between steel wire and cement mortar was developed, based on the interfacial porosity and matrix shrinkage, without conducting pullout test. Firstly, Backscattered Electron test was conducted to determine the interfacial porosity of the steel wire, Nanoindentation test was carried out to determine the elastic modulus of the interfacial zone, restraint ring test was conducted to determine the effective shrinkage deformation of the matrix. The results show that lower interfacial porosity causes higher elastic modulus of interfacial zone, the relationship between interfacial porosity and elastic modulus can be described by a first order fractional function. Then, the extrusion stress between streel wire and matrix was calculated based on the shrinkage deformation of matrix and elastic modulus of interfacial zone. Finally, the frictional bonding strength of interface was calculated based on the extrusion stress and friction coefficient. The calculated frictional bonding strengths for steel wire embedded in mortar with water-cement ratios of 0.25, 0.35, 0.45 and 0.55 are 4.24 MPa, 3.52 MPa, 2.81 MPa and 2.45 MPa, which are in good agreement with the measured bond strengths by pullout test. The prediction model can be extended to predict the pullout behavior of smooth plain steel fibers/wires/rebars in cement-based material. Highlights: Quantitative relationship between elastic modulus and porosity was established. The extrusion stress between streel wire and matrix was calculated. A prediction model on bond strength between steel wire and mortar was developed.